2021
DOI: 10.1155/2021/6689443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Translational Considerations for Understanding Depression and Anxiety in Patients with Inflammatory Bowel Disease

Abstract: Depression and anxiety are comorbidities of inflammatory bowel disease (IBD). Though previous studies have proposed a relationship between anxiety, depression, and IBD, causality and directionality are largely unknown. Current and future research in these areas is aimed at exploring the biological underpinnings of this relationship, specifically pertaining to small molecule metabolism, such as tryptophan. Tryptophan is acquired through the diet and is the precursor to several vital bioactive metabolites includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…This can lead to altered levels of tryptophan, a precursor to several vital bioactive metabolites, and the neurotransmitter serotonin, resulting in depression in these patients. 16 The pro-inflammatory state in IBD patients can cause activation of various inflammation-related processes, including platelet activation factor hyperactivity, oxidative stress, and cellular damage. These mechanisms can contribute to adverse neurobiological outcomes, supporting the prevalence of depression in the IBD population.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to altered levels of tryptophan, a precursor to several vital bioactive metabolites, and the neurotransmitter serotonin, resulting in depression in these patients. 16 The pro-inflammatory state in IBD patients can cause activation of various inflammation-related processes, including platelet activation factor hyperactivity, oxidative stress, and cellular damage. These mechanisms can contribute to adverse neurobiological outcomes, supporting the prevalence of depression in the IBD population.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have previously been shown to be altered in IBD compared with healthy controls. 20 Furthermore, xenobiotic metabolism via CAR/PXR signaling pathways was also increased in the ileum. Recent data demonstrate that bile acids absorbed in the ileum upregulate the xenobiotic transporter MDR1 and protect against inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…26,38 In contrast, metabolic pathways were upregulated in CD11b þ cells of the ileum, also likely in response to the ileal environment where nutrient absorption mainly takes place. Many of the altered metabolic pathways included known microbiota-produced metabolites, such as serotonin 20 and bile acids, 21 and could stem from IBD-linked dysbiosis. Coanalyzing microbiome and metabolomic data with gene expression data would enhance our understanding of their interplay within IBD.…”
Section: Differential Gene Expression In Cd11b þ Cells Is Linked To E...mentioning
confidence: 99%
“…Our study results showed that even in the remission period, the prevalence of anxiety was 33.3%, and depression was 22.2%, which was more than twice the incidence of anxiety and depression in healthy individuals. Anxiety and depression are more prevalent in UC patients with remission due to repeated illnesses, hormones, economic hardship, and other factors (Sidebottom et al, 2021 ). In some clinical studies, anxiety and depression trigger disease recurrence, surgery, or hospitalization (Regueiro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%